2020
DOI: 10.18406/2316-1817v11n420191412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nonlinear models for the description of carbon mineralization in soils treated with pig slurry

Abstract: One of the strategies to reduce environmental impacts caused by pig slurry is its application to soils for agricultural productions. Carbon mineralization curves can be used to determine the best periods for the use of organic matter for an adequate management of soils and growing plants. The objective of this study was to evaluate the fit of nonlinear models for soil carbon mineralization. The experiment was conducted using a randomized block design with four replications and four treatments. The treatments c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It can be seen that there was no overlap in the confidence intervals of the parameter C 0 , which indicates the potentially mineralizable carbon content of the soil and other treatments. The addition of legumes to the soil stimulated microbial activity, leading to increased mineralization of carbon from the legumes in the soil and degradation of native soil organic matter (PAULA et al, 2019;FERNANDES et al, 2011). In addition, there was no overlap in the parameter C 0 of the S. aterrimum, S. mucunoides, and A. pintoi treatments, indicating that the carbon mineralization in the A. pintoi treatment was higher than in the other two, as also observed by Matos et al (2008) In Table 2, by the confidence intervals of the parameter β, which indicates the abscissa of the inflection point-that is, how many hours are needed to reach the maximum point of mineralization related to microbial activity -,there was no overlap between the interval of the soil and the legume treatments, indicating that, with the addition of the plant, the maximum rate of mineralization occurred later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that there was no overlap in the confidence intervals of the parameter C 0 , which indicates the potentially mineralizable carbon content of the soil and other treatments. The addition of legumes to the soil stimulated microbial activity, leading to increased mineralization of carbon from the legumes in the soil and degradation of native soil organic matter (PAULA et al, 2019;FERNANDES et al, 2011). In addition, there was no overlap in the parameter C 0 of the S. aterrimum, S. mucunoides, and A. pintoi treatments, indicating that the carbon mineralization in the A. pintoi treatment was higher than in the other two, as also observed by Matos et al (2008) In Table 2, by the confidence intervals of the parameter β, which indicates the abscissa of the inflection point-that is, how many hours are needed to reach the maximum point of mineralization related to microbial activity -,there was no overlap between the interval of the soil and the legume treatments, indicating that, with the addition of the plant, the maximum rate of mineralization occurred later.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that there was no overlap in the confidence intervals of the parameter C 0 , of the soil and other treatments. The addition of legumes to the soil stimulated microbial activity, leading to increased mineralization of carbon from the legumes in the as well as degradation of native organic matter (PAULA et al, 2019;FERNANDES et al, 2011). Furthermore, there was no overlap in the parameter C 0 of the S. aterrimum, S. mucunoides, and A. pintoi treatments, indicating that the carbon mineralization in the S. aterrimum and S. mucunoides treatments was lower than in the A. pintoi treatment, a result similar to that obtained by Matos et al (2008) In Table 3, by the confidence intervals of the parameter β, it can be observed that there was overlap between the confidence interval of the soil and the legume treatments, and due to this fact, the Logistic model provided a better fit for the treatment with soil only (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Pulrolnik (2019) stresses that at the beginning of organic waste decomposition in soil, the amount of mineralized carbon is higher due to the presence of easily degradable substance fractions, and then this amount reduces, as more resistant carbon fractions are mineralized. This process has been described by nonlinear regression models, since they provide adequate adjustments (PAULA et al, 2019;SILVA et al, 2019a,b) and their parameters allow practical interpretation (MIRANDA et al, 2021;JANE et al, 2020a;SILVA et al, 2020c;SILVA et al, 2021a). Paula et al (2019) and Manzoni and Porporato (2007) highlight the importance of studying carbon mineralization curves and knowing the statistical model that describes the processes as a function of time, considering the need to understand the dynamics of organic waste decomposition, which can help in the soil management practices more favorable to agricultural crop production.…”
Section: Nonlinear Modeling Of Carbon Dynamics In Soil Treated With T...mentioning
confidence: 99%
“…The greater amount of organic matter and the presence of easily decomposing substances favor carbon mineralization at the beginning of the process, that is, the decomposition dynamics occur at decreasing rates, as the organic material is mineralized (PULROLNIK, 2009;MOREIRA;SIQUEIRA, 2006), consequently, the release of other nutrients to the soil occurs. These processes can be described by nonlinear models (PAULA et al, 2019;SILVA, 2005;SILVA et al, 2019a;SILVA et al, 2019b;ZEVIANI et al, 2012;OLIVEIRA et al, 2013). The knowledge of the carbon (C) mineralization dynamics in the soil is essential for the development of appropriate practices in the soil use, being indicative of the organic residues contributing to the demand of trees throughout the crop cycle (BARRETO et al, 2010;GODINHO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In litter soils, it may be that the mineralization process has two phases of mineralization, one phase due to easily mineralizable substances and another phase due to the more resistant substances. In processes with two phases, the use of the Cabrera model has shown a good fit (PAULA et al, 2019;SILVA et al, 2019a;SILVA et al, 2019b;ZEVIANI et al, 2012;PEREIRA et al, 2009).…”
Section: Introductionmentioning
confidence: 99%